Integrating Technology into English Language Teaching in Uzbekistan - Rohila Khidirboeva Saparboy qizi (Scientific Trends, 2025)
This paper examines the role of modern information and communication technologies (ICT) in the teaching of English in Uzbekistan. While digital resources such as interactive applications, multimedia, and online platforms have greatly increased student motivation and participation, teachers still face challenges connected with poor infrastructure, limited training, and outdated equipment. The research, which included surveys and interviews with 35 teachers from various regions, highlights that a proper balance between technological support and teacher readiness is essential. The study recommends greater investment in ICT infrastructure, professional training for teachers, and the development of locally adapted e-learning materials.
Keywords: English language teaching, ICT, Uzbekistan, EFL, digital learning, opportunities, challenges.